EFEKTIVITAS PROGRAM KERJA UNIT PENDIDIKAN MASYARAKAT DAN REKAYASA (DIKYASA) SATLANTAS POLRESTA PEKANBARU TAHUN 2015 - Yola Fransiska; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pekanbaru city which is the capital of Riau province, continue doing development in various fields for the realization of Pekanbaru city as a metropolitan city that is civil, it must be prepared. The real problems faced by the city of Pekanbaru one of which is the bottleneck. Congestion is one of the negative impact from the more advanced development, especially in the field of production of motor vehicles that cause heavy traffic. This is because not match the number of vehicles with an area of road that will eventually allow traffic accidents and cause discomfort for the users of the highway. The institutions authorized and responsible for the traffic conditions are particularly Pekanbaru Police Satlantas unit public education and traffic engineering (Dikyasa). In order to realize traffic conditions in an orderly, safe, and comfortable work program implemented by Dikyasa. The work program is meant socialization, education seminars or for the public to be aware and orderly traffic. The concept of the theory used is effectiveness (Mahmudi:2015). This study uses descriptive qualitative research. In collecting the data, the authors use the technique of interview, observation and documentation. By using key informants as a source of information and analysis of data. The results of this study lead to the conclusion that the effectiveness of the Work Program Unit (Dikyasa) Police Satlantas Pekanbaru, has not been applied effectively because still there is a problem in the input, namely: human resources are still not adequate in terms of quality and quantity, sources of funding available is not sufficient to carry out the work program, the use of technology has not been utilized to the maximum. With the problems that occurred in the input section, it will affect the results of the work program Pekanbaru Police Satlantas Dikyasa unit. Input troubled course will affect the process, outputs and outcomes or results obtained. In addition, factors that influence the effectiveness of the implementation of the work program is community participation. Therefore, the need for additional personnel, improvement of the budget system, the use and mastery of technology, and give a good example to promote public participation. Keywords: Effectiveness, Work Program, Dikyasa